The Use of Inclusive Language in the Speech of University Teachers and Students (2022)
The aim of this mixed research was to analyze the attitude of teachers and students who belong to the Language School of the Universidad Veracruzana towards the use of inclusive language. It is considered that the language tends to reproduce a type of order when it comes to gender, in which women and people with different gender identities tend to be excluded. Thus, it was deemed appropriate to deepen in the current perspectives on inclusive language within a school community that is dedicated to study languages. A survey was administered and the results show contrasting opinions. There is a negative attitude among some of the participants that are reluctant to use inclusive language as they consider it irrelevant and a passing trend. However, there are some others who seem to have a rather open attitude, as they stated that inclusive language leads towards the reflection and the combination of multiple linguistic creations